PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TS-TS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA - Anes Marsela (Epsilon: Jurnal Pendidikan Matematika, 2020)
The problem that the author encountered in class X SMK Palapa Bandar Lampung is the low ability of mathematical communication. The purpose of the study was to determine the difference in average mathematical communication skills of students who use the Two Stay Two Stray (TS-TS)cooperative learning model with TS-TS using the Conventional learning model in class X students even semester of SMK Palapa Bandar Lampung. This study used an experimental method, the population of the study was 123 students of SMK Palapa Bandar Lampung, samples taken using the Random Sampling Cluster technique, namely the X PM class as the Experiment class and the AP X Class as the Control class. Students' mathematical communication skills are carried out with an essay test which amounts to 6 questions which are first tested for their validity and reliability. From the results of testing the hypothesis using the t-test obtained thit = 4.94 from the t distribution table at a significant level of 5% known tdaf = 1.67. So thit > tdaf so that it can be concluded that "There is an Effect of the Application of the Two Stay Two Stray Cooperative Learning Model (TS-TS) on the Mathematical Communication Ability of Class X Students in the even semester of SMK Palapa Bandar Lampung